Analisis Tingkat Pengetahuan Keracunan Timbal (Pb) dan Karbon Monoksida (CO) dengan Kadar Hemoglobin pada Pekerja Luar Ruangan - Aulia Mutiara Hikmah (Universitas Muhammadiyah Manado, 2024)
Air pollution can lead to exposure to substances from exhaust gases. Carbon monoxide (CO) and lead (Pb) are harmful substances that can negatively impact the health of outdoor workers. Workers such as street sweepers and waste collectors are particularly susceptible to these exposures due to their daily street activities. Therefore, health assessments, such as hemoglobin (Hb) examinations, are essential. This study involved a literature review, distribution of questionnaires, interviews with the research population, laboratory tests, and analysis of the results. The study included 67 respondents, the majority of whom were male (97%) and in the productive age group of 21–40 years (62.7%). Most respondents worked more than 8 hours daily (91%), increasing their risk of exposure to hazardous substances. The results showed that 65.7% of respondents had normal hemoglobin levels, 32.8% had elevated levels, and 1.5% had low levels. Workers' knowledge about the dangers of Pb and CO (70.1%) showed no significant correlation with hemoglobin levels. However, knowledge remains crucial for encouraging protective behaviors such as the use of personal protective equipment. This study highlights the importance of education and safety training to protect the health of outdoor workers.